MALDI-TOF for the rapid detection of carbapenemase-producing Enterobacteriaceae: comparison of the commercialized MBT STAR®-Carba IVD Kit with two in-house MALDI-TOF techniques and the RAPIDEC® CARBA NP. (11th June 2018) - Dortet, Laurent; Tandé, Didier; de Briel, Dominique; Bernabeu, Sandrine; Lasserre, Camille; Gregorowicz, Guillaume; Jousset, Agnès B; Naas, Thierry
Abstract: Objectives: There is an urgent need for accurate and fast diagnostic tests to identify carbapenemase-producing bacteria. Here, we have evaluated three MALDI-TOF-based techniques to detect carbapenemase-producing Enterobacteriaceae (CPE) from cultured colonies. Methods: The performance of three MALDI-TOF-based techniques, including the commercialized MBT STAR ® -Carba IVD Kit (Bruker Daltonics) and two in-house protocols performed on the Microflex LT Biotyper (Bruker Daltonics) and the VITEK ® MS Plus (bioMérieux), were compared with those of the RAPIDEC ® CARBA NP (bioMérieux). A collection of 175 isolates including 120 carbapenemase producers and 55 non-carbapenemase producers was tested. Samples were tested blind in the three participating centres. The repeatability of the MBT STAR ® -Carba IVD Kit was also evaluated. Results: The three MALDI-TOF techniques possess sensitivities ranging from 95% to 100% and specificities from 98.2% to 100% compared with 99.2% and 100%, respectively, for the RAPIDEC ® CARBA NP. The MBT STAR ® -Carba IVD Kit gave highly reproducible results and is the only technique able to provide a concomitant identification of the bacterial isolate. The three MALDI-TOF techniques possess a fast turnaround time (less than 1.5 h). Conclusions: Overall, MALDI-TOF is a reliable technique for the rapid detection of CPE from cultured colonies. MBT STAR ® -Carba IVD Kit, the only commercially available assay, could easily be implemented in a clinical microbiology laboratory if it is already equipped with a Microflex LT Biotyper mass spectrometer.